2015
DOI: 10.5665/sleep.4516
|View full text |Cite
|
Sign up to set email alerts
|

Lucid Dreaming in Narcolepsy

Abstract: Narcolepsy is a novel, easy model for studying lucid dreaming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 32 publications
5
83
1
2
Order By: Relevance
“…The whole picture suggests a strong relationship between fast‐frequency EEG activity and effectiveness of memory encoding of dream experience as prerequisite for its successful recall after awakening and prompts to consider in future studies also the relationship of dream recall with frequencies faster than beta. This relationship appears plausible because (1) the power in the higher gamma range is associated with dreaming both during REM and NREM sleep; (2) changes in gamma coherence are linked to lucid dreams during REM sleep in NT1 patients, and (3) transcranial direct current stimulation (tDCS) in the gamma band during REM sleep can induce lucid dreaming in healthy subjects …”
Section: Discussionmentioning
confidence: 99%
“…The whole picture suggests a strong relationship between fast‐frequency EEG activity and effectiveness of memory encoding of dream experience as prerequisite for its successful recall after awakening and prompts to consider in future studies also the relationship of dream recall with frequencies faster than beta. This relationship appears plausible because (1) the power in the higher gamma range is associated with dreaming both during REM and NREM sleep; (2) changes in gamma coherence are linked to lucid dreams during REM sleep in NT1 patients, and (3) transcranial direct current stimulation (tDCS) in the gamma band during REM sleep can induce lucid dreaming in healthy subjects …”
Section: Discussionmentioning
confidence: 99%
“…In the case of sleep-related conditions, researchers have linked narcolepsy with changes in dream mentation. Particularly, higher dream recall frequency and lucid dreaming (Dodet et al, 2015;Rak et al, 2015). Recent work has also reported an association between narcolepsy and creativity (Lacaux et al, 2019).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 96%
“…Of note, up to 78 % of patients with Narcolepsy are lucid dreamers. 36 Intriguingly, it has been reported that healthy subjects during REM sleep may generate some "conscious" experience (reflexive consciousness), showing that the brain still keeps the capacity to detect and categorize internal states of mind. 36 Moreover, recently Mazza et al 37 reported the observation of a patient who, while being recorded with intra-cerebral electrodes for refractory epilepsy, was able to reproduce during REM sleep a motor behavior performed during wakefulness with EEG activity comparable to that of wakefulness over the prefrontal and parietal areas and over the anterior cingulate cortex.…”
Section: Within-mind Dissociation: Lucid Dreamingmentioning
confidence: 99%